1989
DOI: 10.1063/1.101244
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic cross phase modulation in ZnSe

Abstract: The temporal profiles of harmonic cross phase modulation pulses from 500 to 570 nm generated in ZnSe by a 1054 nm picosecond pulse have been observed and theoretically modeled. The pulse shape of these harmonic-modulated pulses is accounted for by the interference and induced phase matching of the harmonic generated waves in ZnSe by cross phase modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…One factor that can alleviate the remaining phase mismatch is the influence of self-phase modulation (SPM) of the fundamental on sideband/harmonic generation, which is known as cross-phase modulation (XPM). [47][48][49] Under the excitation conditions used, significant phase shifts due to SPM are expected to occur in the MIR beam. For example, using ~ 2 × 10 10 W/cm 2 at a wavelength of 3.5 µm passing through 350 µm of GaAs, the estimated intensity-induced phase shift is ~ 1 radian.…”
Section: Shown Inmentioning
confidence: 99%
“…One factor that can alleviate the remaining phase mismatch is the influence of self-phase modulation (SPM) of the fundamental on sideband/harmonic generation, which is known as cross-phase modulation (XPM). [47][48][49] Under the excitation conditions used, significant phase shifts due to SPM are expected to occur in the MIR beam. For example, using ~ 2 × 10 10 W/cm 2 at a wavelength of 3.5 µm passing through 350 µm of GaAs, the estimated intensity-induced phase shift is ~ 1 radian.…”
Section: Shown Inmentioning
confidence: 99%
“…When, apart from SHG, third-order nonlinear optical processes are important, it was shown that the generated second harmonic acquires a very complicated multipeak structure [11,12]. This structure is the result of the phase modulation caused by the third-order processes selfphase-modulation (SPM) and induced phase modulation (IPM) coupled with the interference eff'ects in the SHG process.…”
Section: Introductionmentioning
confidence: 99%
“…) neously with cross-phase modulation, which affects both the temporal and spectral properties of second harmonic pulses. In this section, measurements of XPM on the second harmonic generated by an intense primary picosecond pulse in ZnSe crystals are reported (Alfano et al, 1987a;Ho et al, 1988).…”
Section: Harmonic Cross-phase Modulation Generation In Znsementioning
confidence: 99%
“…The first experimental observation of XPM spectral effects dates to early 1986, when it was reported that intense picosecond pulses could be used to enhance the spectral broadening of weaker pulses copropagating in bulk glasses (Alfano et al, 1986). Since then, several groups have been studying XPM effects generated by ultrashort pump pulses on copropagating Raman pulses (Schadt et al, 1986;Schadt and Jaskorzynska, 1987a;Islam et al, 1987a;Alfano et al, 1987b;Baldeck et al, 1987b-d;Manassah, 1987a, b;Hook et al, 1988), second harmonic pulses (Alfano et al, 1987a;Manassah, 1987c;Manassah and Cockings, 1987;Ho et al, 1988), stimulated four-photon mixing pulses , and probe pulses (Manassah et al, 1985;Agrawal et al, 1989a;Baldeck et al, 1988a, c). Recently, it has been shown that XPM leads to the generation of modulation instability (Agrawal, 1987;Agrawal et al, 1989b;Schadt and Jaskorzynska, 1987b;Baldeck et al, 1988bBaldeck et al, , 1988dGouveia-Neto et al, 1988a, b), solitary waves (Islam et al, 1987b;Trillo et al, 1988), and pulse compression (Jaskorzynska and Schadt, 1988;Manassah, 1988;Agrawal et al, 1988).…”
Section: Introductionmentioning
confidence: 99%